Seismic performance of timber band in dry stone masonry building - Parajuli, Hari Ram; Regmi, Kapil (Journal of Innovations in Engineering Education, 2022)
This study has been carried out to determine the performance of dry stone masonry building using FEA with an approach of the macro-modeling using Solid 65 as a element for the modeling. The solution method used for the subject model was implicit. Concrete damaged plasticity model was selected for this study which can describe the behavior in tension and compression with non-linearity in plastic range. In the first Model (M1), unreinforced masonry is considered whereas in the second model (R1), unreinforced masonry reinforced with timber laces were considered. The capacity of both the buildings was evaluated in terms of base shear versus roof displacement plot. The performance of the building was also determined by plotting the capacity curve and demand curve in the same graph using FEMA 356. For the assessment of the dry stone masonry building two types of analysis were performed; a modal analysis and a pushover analysis. The analysis was mainly focused on the Pushover analysis, while the modal analysis was used to understand the behavior of the structure under a free vibration. The first mode time period of the Model R1 was found decreased by 31.65% than that of model M1. Also, the capacity of model R1 was found increased by 45% and 49.74% in case of x-direction and y-direction respectively. It was found that the performance of dry stone masonry building reinforced with timber laces was better in stregnthening the seismic property of building.